Pemanfaatan Limbah Tembakau Puntung Rokok Menjadi Larutan Multifungsi Yang Berperan Sebagai Biopestisida Dan Pupuk Organik Cair (POC) - BIPEPO Dalam Satu Waktu Pengaplikasian - Mikola, Ananda; Azhari, Afifah Nadia; Zidan, Syarif M Faiz; Jati, Dian Rahayu (Universitas Tanjungpura, 2024)
Organic fertilizers that are composed of living things, such as weathering the remains of plants, animals, and humans. Organic fertilizers can be in the form of solid or liquid which are used to improve the physical, chemical, and biological properties of the soil. The source material used in this study is a multifunctional solution that acts as a biopesticide and liquid organic fertilizer. This solution uses raw materials in the form of tobacco butts waste, orange peel waste, watermelon waste and citronella leaf extract. This solution is through laboratory testing. The purpose of this study was to determine the effectiveness of the multifunctional solution on the plants to be tested. The results obtained from testing the solution on plants, namely the effectiveness of the BIPEPO solution was declared successful, indicated by the control plants from chilies dying from being attacked by pests, while the other plants that were applied to the BIPEPO solution were still fresh and not attacked by pests. The accurate application of BIPEPO solution is by spraying it on the ground.